Needs Analysis the Importance of Improving Teacher’s Competence in Facilitating Student-Centered Learning - Sutrisno, Sutrisno; Badeni, Badeni; Risdianto, Eko (PPSDP International Journal of Education, 2024)
This study aims to analyze the need for improved teacher competency at the Al Fida Foundation in Bengkulu City to facilitate student-centered learning. With a qualitative approach, data were collected through interviews and questionnaires involving teachers with at least three years of teaching experience. The findings indicate that training in the use of information technology, especially the Learning Management System (LMS), is greatly needed. Although teachers understand learning planning, they have difficulty integrating learning resources and instructional strategies that encourage student interest. Time constraints and suboptimal structural support are the main challenges. This study provides a new perspective on the analysis of teacher competency needs in private schools in the context of student-centered learning. The results of this study identify training needs and offer competency improvement strategies that can be implemented by educational foundations.